Risk of infection following colonoscopy and sigmoidoscopy in symptomatic patients - Lin, Jiun-Nong; Wang, Chang-Bi; Yang, Chih-Hui; Lai, Chung-Hsu; Lin, Hsi-Hsun (Endoscopy, 2017)
Background and study aims Previous studies describing the incidence of infection after colonoscopy and sigmoidoscopy are limited. The aim of this study was to determine the incidence of infection, and to propose a nomogram to predict the probability of infection following colonoscopy and sigmoidoscopy in symptomatic patients. Patients and methods A nationwide retrospective study was conducted by analyzing the National Health Insurance Research Database of Taiwan. The incidence of infection within 30 days after colonoscopy and sigmoidoscopy was assessed and compared with a control group matched at a ratio of 1:1 based on age, sex, and the date of examination. Results  In all, 112 543 patients who underwent colonoscopy or sigmoidoscopy and 112 543 matched patients who did not undergo these procedures were included. The overall incidence of infection within 30 days after colonoscopy and sigmoidoscopy was 0.37 %, which was significantly higher than that of the control group (0.04 %; P < 0.001). Diverticulitis, peritonitis, and appendicitis were the most common infections. Patients who underwent colonoscopy or sigmoidoscopy had a 9.38-fold risk of infection (95 % confidence interval, 6.81 – 12.93; P < 0.001) compared with the control group. The predicted infection-free rates of the nomogram were closely aligned with the actual infection-free rates, with a bootstrapping concordance index of 0.763. Conclusions Colonoscopy and sigmoidoscopy are associated with an increased risk of infection, which may occur after these procedures. Our nomogram may provide clinicians with an easy tool to evaluate the risk of infection after colonoscopy and sigmoidoscopy in symptomatic patients.